Daniel J. Evans : an autobiography - Evans, Daniel J., 1925- (Office of the Secretary of State, Legacy Washington, 2021)
The remarkable story of Dan Jackson Evans' life from childhood to active retirement, from three-term governor of the Evergreen State to U.S. Senator in the "other" Washington.